Safety on navigation in the straits of Malacca using Automatic Identification System (AIS) data - Amirrudin Yaacob, 1987-; Jaswar Koto, supervisor; Fakulti Kejuruteraan Mekanikal (2014)
Thesis (Sarjana) - Universiti Teknologi Malaysia, 2014